Single incision laparoscopic surgery (SILSTM) using an umbilical hernial approach for cryptorchidectomy of a degenerated testis in a dog - Tiosso,Caio de Faria (2019)
ABSTRACT: SILSTM via an umbilical hernia opening was used in the correction of an abdominal cryptorchidism in a dog. The SILSTMport was inserted through a 2.5 cm skin incision on the umbilical hernia and pneumoperitoneum was established with CO2. A 10mm telescope, 5mm laparoscopic Babcock clamp, and a clamp with combined cutting and coagulation features were used for the dissection and removal of the testicle through the SILSTM port. The treatment proved to be effective, easy, and quick to perform. However, the lack of triangulation between clamps and telescope limited the movement of the instruments, making it more laborious than a multiple-trocar approach. It can be concluded that the use of a SILSTM port through a pre-existing opening of the abdominal wall enables a reduction of the risks associated with multiple incisions; such as injury and manipulation of internal organs, pain, bleeding, and development of new hernias.